Efficacy of Recombinant Circumsporozoite Protein Vaccine Regimens against Experimental Plasmodium falciparum Malaria - Kester, Kent E.; McKinney, Denise A.; Tornieporth, Nadia; Ockenhouse, Christian F.; Heppner, D. Gray; Hall, Ted; Krzych, Urszula; Delchambre, Martine; Voss, Gerald; Dowler, Megan G.; Palensky, Jolie; Wittes, Janet; et al. (The Journal of infectious diseases, 2001)
After initial successful evaluation of the circumsporozoite-based vaccine RTS,S/SBAS2, developed by SmithKline Beecham Biologicals with the Walter Reed Army Institute of Research, protective efficacy of several regimens against Plasmodium falciparum challenge was determined. A controlled phase 1/2a study evaluated 1 or 2 standard doses of RTS,S/SBAS2 in 2 groups whose members received open-label therapy and 3 immunizations in blinded groups who received standard, one-half, or one-fifth doses. RTS,S/SBAS2 was safe and immunogenic in all groups. Of the 41 vaccinees and 23 control subjects who underwent sporozoite challenge, malaria developed in 7 of 10 who received 1 dose, in 7 of 14 who received 2 doses, in 3 of 6 who received 3 standard doses, in 3 of 7 who received 3 one-half doses, in 3 of 4 who received 3 one-fifth doses, and in 22 of 23 control subjects. Overall protective efficacy of RTS,S/SBAS2 was 41% (95% confidence interval, 22%–56%; P = .0006). This and previous studies have shown that 2 or 3 doses of RTS,S/SBAS2 protect against challenge with P. falciparum sporozoites.